Infrastructure evaluation of anganwadi centres in Kalaburagi city: a cross sectional study - Baseer, Mohammed Abdul; Ansari, Khusroo Ahmed; Takalkar, Anant A. (International Journal Of Community Medicine And Public Health, 2021)
Background: ICDS scheme represents one of the largest programmes, which is a symbol of India’s commitment to its children, providing pre-school education on one hand and breaking the today vicious cycle of malnutrition, morbidity, reduced learning capacity and mortality on the other hand. Methods: The present study was taken up to assess the infrastructure and services of anganwadi centers. Community based cross sectional observational study was conducted by involving 92 anganwadi centers in Kalaburagi city. Results: Out of 92 AWCs studied, 52 (56.5%) were belonged to Government set up whereas 40 i.e.; 43.5% were on rental basis. Safe drinking water was available in 81 i.e.; 88% of AWCs, toilet facility was available in 34 i.e.; 37% of AWCs. Adequate outdoor space was available in 54 i.e.; 58.7% of AWCs. Adequate indoor space was available in 72 i.e.; 78.3% of AWCs. Adequate kitchen space was available in 65 i.e.; 70.7% of AWCs. Adequate food storage facility was available in 70 i.e.; 76.1% of AWCs and in 22 i.e.; 23.9% it was not adequate. In 30 i.e.; 32.6% of AWCs, source of fuel use was LPG. Conclusions: Safe drinking water was available in majority of AWCs. Almost one third of anganwadi have inadequate space. Majority of anganwadi have maintained sufficient number of registers. Outdoor and indoor game kits and equipment’s were available at majority of AWCs.